The Legacy of poverty, Marginalization and Underdevelopment in Balochistan :Historical ,Political and Social Factors - Jabeen, Dr.Musarrat (Hanken, 2009)
The process of marginalization symphonizes poverty and underdevelopment Economic development entails the laxation of an area in international system as economic advantage defines the pursuit of nation state system. The economic development can not be cherished without a match with the social political capital of relevant area. This paper narrates the story of marginalization of Balochi in excess by burgeon regional and international economic interests. The study is significant to flash balochistan in politics of international economic system. In globalized world the area has to be interjected with national and international imperatives of economic conflict leads to propose3.D strategy for management of economic development includes.